Assessment of Geotechnical Hazard due to Deep Excavations in Bogota Clays: A Contribution for Sustainability in Urban Environments (2020)
The development of resilient and sustainable cities considers the construction of infrastructure projects that involve deep excavations. During excavations, surface displacements frequently occur that may be inadmissible for previously constructed elements of the urban environment, threatening the sustainability of already consolidated sectors. In this article, we present an approximation to the estimation of the geotechnical hazard  by deep excavations in soft lacustrine soils of Bogotá, DC, using parametric numerical simulations that sought to establish the probability of occurrence of base bottom heave, and the estimation of surface displacements for variable excavation geometries. A database was consolidated from 85 projects found in geotechnical zones having soft soils in the city. From this base, statistically representative values of shear strength and stiffness were determined, and a statistically representative geotechnical profile of the lacustrine clays was prepared for parametric analyzes. The hazard estimation was developed in three stages: construction of the geotechnical model, approach of hazard scenarios and determination of the hazard level. The following parameters were considered: excavation geometry (base and height), safety factor, failure probability and vertical ground displacements (settlements). Finally, a matrix is ​​presented to determine the hazard level by excavations in the soft soils of Bogotá, whose data provide a prior assessment that contributes to promoting resilience and sustainability of already developed areas.